1974
DOI: 10.1271/nogeikagaku1924.48.459
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Phytol from the Hiziki Unsaponifiable Matter and Its Activating Effect on Pancreatic Lipase Activity

Abstract: In the previous report, the residual fraction (residue) after extraction of fucosterol from the unsaponifiable matter of Hizikia fusiformis (hiziki) was found to possess essentially the same remarkable accelerating activity on pig pancreatic lipase as that of the unsaponifiable matter. Hence, the isolation and identification of the active principles from the residue were attempted, and the activity of three activators was investigated.One of the activators isolated from the residue was identified as phytol, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1982
1982
1983
1983

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We have thus far studied the isolation and characterization of the activator, which stimulates markedly the hydrolysis of triacetin (TAesterase activity) by a porcine pancreatic lipase preparation, from the marine brown alga Hizikia fusiformis (hiziki).l -8) It has been found that phytol 6 ) isolated from hiziki is a typical activator of this kind, and recently that parathion 9 ) as well as retinol 10 ) exhibits a remarkable stimulating action, essentially similar to that observed with phytol, on the TAesterase activity.…”
mentioning
confidence: 99%
“…We have thus far studied the isolation and characterization of the activator, which stimulates markedly the hydrolysis of triacetin (TAesterase activity) by a porcine pancreatic lipase preparation, from the marine brown alga Hizikia fusiformis (hiziki).l -8) It has been found that phytol 6 ) isolated from hiziki is a typical activator of this kind, and recently that parathion 9 ) as well as retinol 10 ) exhibits a remarkable stimulating action, essentially similar to that observed with phytol, on the TAesterase activity.…”
mentioning
confidence: 99%